1996
DOI: 10.1136/adc.75.5.399
|View full text |Cite
|
Sign up to set email alerts
|

Needs of disabled children and their families.

Abstract: for use by child development centres and teams. The development of an alternative approach, using a series of statements of good practice, is described. Parents of children with cerebral palsy were asked to participate in semistructured interviews, to ascertain the value and relevance of these quality statements. Parents were most concerned about the standard of news breaking and early follow up, the sharing of information, and the supply and repair of equipment. The findings were used to modify the quality ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
20
0

Year Published

1997
1997
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 21 publications
0
20
0
Order By: Relevance
“…Different models might be more suitable in other settings in the United Kingdom T he time around diagnosis is a key milestone for the parents of children with disabilities or chronic disorders. [1][2][3][4][5][6][7] The potential value of a family "key worker" in promoting information provision, emotional support, and liaisons among different agencies and services has long been discussed, [8][9][10] but such services have not been extensively implemented. We report the effects on the health service experiences of parents and the practices of health care professionals of a novel, hospital-based, key worker service within a tertiarylevel pediatric ophthalmology department.…”
mentioning
confidence: 99%
“…Different models might be more suitable in other settings in the United Kingdom T he time around diagnosis is a key milestone for the parents of children with disabilities or chronic disorders. [1][2][3][4][5][6][7] The potential value of a family "key worker" in promoting information provision, emotional support, and liaisons among different agencies and services has long been discussed, [8][9][10] but such services have not been extensively implemented. We report the effects on the health service experiences of parents and the practices of health care professionals of a novel, hospital-based, key worker service within a tertiarylevel pediatric ophthalmology department.…”
mentioning
confidence: 99%
“…Caregivers' need for further infor mation has been highlighted in studies in various settings -from Botswana (Brodin and Molosiwa 2000) and Uganda (Hartley et al 2005) to the United Kingdom (Milner et al 1996), and Australia (Dyke et al 2006) and sug gest that this is a universal need and one which therapy services do not always adequately address.…”
Section: Discussionmentioning
confidence: 99%
“…It is a lifelong condition, and the goal of a rehabilitation service is to help the child and family function in the most effective way possible (Milner et al 1996). The value of familycentred principles in guiding the delivery of paediatric reha bilitation services has been advocated in the literature for a number of years, but only recently have paediatric service providers been able to base their prac tices on the evidence for familycentred services (FCS) and not merely on recom mendations (Dyke et al 2006).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Surveys of both parents and professionals (King, King, & Rosenbaum, 1996;Milner, Bungay, Jellinek, &: Hall, 1996;Rosenbaum, King, &c Cadman, 1992) as well as scholarly writing (Kolobe, 1991;Peterson & Cooper, 1989) have suggested that parental participation is crucial for improving performance in children with physical disabilities.…”
mentioning
confidence: 97%